Balance Function in High-Energy Collisions - A. Tawfik; Asmaa G. Shalaby (Advances in High Energy Physics)
Aspects and implications of the balance functions (BF) in high-energy physics are reviewed. The various calculations and measurements depending on different quantities, for example, system size, collisions centrality, and beam energy, are discussed. First, the different definitions including advantages and even short-comings are highlighted. It is found that BF, which are mainly presented in terms of relative rapidity, and relative azimuthal and invariant relative momentum, are sensitive to the interaction centrality but not to the beam energy and can be used in estimating the hadronization time and the hadron-quark phase transition. Furthermore, the quark chemistry can be determined. The chemical evolution of the new-state-of-matter, the quark-gluon plasma, and its temporal-spatial evolution, femtoscopy of two-particle correlations, are accessible. The production time of positive-negative pair of charges can be determined from the widths of BF. Due to the reduction in the diffusion time, narrowed widths refer to delayed hadronization. It is concluded that BF are powerful tools characterizing hadron-quark phase transition and estimating some essential properties.